PAI Teacher's Strategy In Developing Student's Emotional Intelligence - Lutfi Fadilah; Adi Wijaya (Journal of Contemporary Islamic Education, 2022)
The type of this research is qualitative approach, with the background of MAN 1 East Lampung. The methods used in collecting data are interviews, observation, and dokumentation. Data analysis was used the Psychology and Islamic Education approach, by doing data reduction, data presentation, and conclusion drawing. Data validity was tested by triangulation of techniques and sources. The results of this study indicate that strategies used by PAI teachers in developing emotional intelligence of MAN 1 East Lampung students based on aspects of emotional intelligence expressed by Daniel Goleman such as the ability to recognize self-awareness, self-regulation, self-motivation, empathy and social skills, namely by conducting training, applying learning methods, and humanistic approaches. In addition, teachers develop emotional intelligence through Islamic teachings to shape student morals, such as habituation education, spiritual training with worship (riyadah), and efforts to refrain from lust (mujahadah).